INCLUSIVE POLICIES AND SUPPORT SERVICES FOR ACADEMIC ACHIEVEMENT OF STUDENTS TO ACHIEVE SDG-4 AT HIGHER EDUCATION LEVEL - MAMOONA QAMAR, NAEEM ULLAH, MUHAMMAD ANWAR FAROOQ, JAM MUHAMMAD ZAFAR (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
The purpose of the study was to examine the association between inclusive policies and support services that help students in achieving academic success in higher education institutions. Having a particular emphasis on advancing Sustainable Development Goal 4 (SDG-4). The objective is to ensure that all individuals receive high-quality education that is inclusive and equitable. A quantitative survey was conducted that was descriptive in nature at Khwaja Fareed University of Engineering and Information Technology (KFUEIT) in Rahim Yar Khan, Pakistan. Data was collected from 320 students in eight faculties using stratified and simple random sampling. Confirmatory factor analysis confirmed that the self-developed scale of inclusive policies (6 items) and academic achievement (5 items) was valid (KMO =.867, overall <> =.92). The results indicate that 60% of respondents agree that inclusive policies prevent discrimination, while 64% confirm practical accommodations like sign language interpreters and alternative exam formats. The findings show that inclusive policies and support services are not just ethical demands, but they can also have a direct impact on improving educational outcomes. In order to close achievement gaps and meet SDG-4 targets, universities need to focus on the systematic implementation of financial aid, flexible assessments, mental health services, and mandatory diversity training.